Higher abdominal fat area associates with lower donor kidney function before and after living kidney donation - Lisa B. Westenberg; Marco van Londen; Marcel Zorgdrager; Mara A. McAdams-DeMarco; Dorry L. Segev; Stephan J. L. Bakker; Alain R. Viddeleer; Robert A. Pol (Scientific Reports)
Abstract Central body fat distribution affects kidney function. Abdominal fat measurements using computed tomography (CT) may prove superior in assessing body composition-related kidney risk in living kidney donors. This retrospective cohort study including 550 kidney donors aimed to determine the association between CT-measured abdominal fat areas and kidney function before and after donor nephrectomy. Donors underwent glomerular filtration rate measurements (125I-Iothalamate, mGFR) before and 3 months after donation. Linear regression analyses with body surface area (BSA)-standardized and crude mGFR were performed to assess the association of height-indexed tomographic fat measurements with kidney function. In age-, and sex-adjusted analyses higher levels of total abdominal, visceral, subcutaneous, and intramuscular adipose tissue index were significantly associated with lower mGFR levels before donation (BSA-standardized mGFR: visceral adipose tissue index: Βeta=-0.11, p < 0.001, subcutaneous: Βeta=-0.10, p < 0.001, intramuscular: Βeta=-1.18, p < 0.001, total abdominal: Βeta=-0.07, p < 0.001). Higher tomographic abdominal fat is associated with lower BSA-standardized mGFR after donation and a greater decrease in mGFR between screening and 3 months post-donation. This study shows that CT-measured abdominal fat area is associated with kidney function before and after living kidney donation.